A more ecological perspective on human–robot interactions. (5th April 2023) - Ravikumar, Varun; Bowen, Jonathan; Anderson, Michael L.
Abstract: Drawing from two strands of ecological psychology, we suggest that even if social robots are interactive depictions, people need not mentally represent them as such. Rather, people can engage with the opportunities for action or affordances that social robots offer to them. These affordances are constrained by the larger sociocultural settings within which human–robot interactions occur.